Enhancing alcohol screening and brief intervention among people receiving opioid agonist treatment: qualitative study in primary care. Issue 4 (5th December 2016) - McCombe, Geoff; Henihan, Anne Marie; Klimas, Jan; Swan, Davina; Leahy, Dorothy; Anderson, Rolande; Bury, Gerard; Dunne, Colum; Keenan, Eamon; Meagher, David; O'Gorman, Clodagh; O'Toole, Tom; et al.
Abstract : Purpose: Problem alcohol use (PAU) is common and associated with considerable adverse outcomes among patients receiving opioid agonist treatment (OAT). The purpose of this paper is to describe a qualitative feasibility assessment of a primary care-based complex intervention to promote screening and brief intervention for PAU, which also aims to examine acceptability and potential effectiveness. Design/methodology/approach: Semi-structured interviews were conducted with 14 patients and eight general practitioners (GPs) who had been purposively sampled from practices that had participated in the feasibility study. The interviews were transcribed verbatim and analysed thematically. Findings: Six key themes were identified. While all GPs found the intervention informative and feasible, most considered it challenging to incorporate into practice. Barriers included time constraints, and overlooking and underestimating PAU among this cohort of patients. However, the intervention was considered potentially deliverable and acceptable in practice. Patients reported that (in the absence of the intervention) their use of alcohol was rarely discussed with their GP, and were reticent to initiate conversations on their alcohol use for fear of having their methadone dose reduced. Research limitations/impelications: Although a complex intervention to enhance alcohol screening and brief intervention among primary care patients attending for OAT is likely to be feasible and acceptable, time constraints and patients' reticence to discuss alcohol as well as GPs underestimating patients' alcohol problems is a barrier to consistent, regular and accurate screening by GPs. Future research by way of a definitive efficacy trial informed by the findings of this study and the Psychosocial INTerventions for Alcohol quantitative data is a priority. Originality/value: To the best of the knowledge, this is the first qualitative study to examine the capability of primary care to address PAU among patients receiving OAT.